Estrategia de branding para el posicionamiento de un producto cárnico de la microempresa Mafer - Guaraca Roldán, Mónica Maribel (2024)
The research aims to develop a branding strategy to enhance the position of a meat product of the Mafer company in the local market, in the midst of intense competition. A non-experimental, cross-sectional, descriptive-exploratory, field and documentary approach is chosen, with a convergent model and a mixed approach. Analytical, synthetic, inductive, and deductive methods are employed, in addition to surveys, brand quality assessments, and interviews. The sample includes 25 people, selected through a non-probabilistic convenience sampling. The branding strategy focuses on the naming process, the graphic evaluation of the media, the definition of the brand typology and the determination of the brand's life cycle. This strategy is expected to help improve Mafer's market position by differentiating it from the competition and building trust and loyalty among consumers. It is recommended to implement a comprehensive brand management, which includes a communication and promotion campaign, a continuous improvement plan and the execution and evaluation of the branding strategy, in line with the standards of quality, differentiation and value of the brand. This approach will ensure a strong and long-lasting presence in the market, establishing close links with customers.